Antibacterial Potential of Curcuma Mangga Kombucha: The Effect of Fermentation Duration on Activity Against Escherichia coli and Salmonella typhi - Ratna, Ratna; Anjani, Gemala; Nur Afifah, Diana; Ayustaningwarno, Fitriyono; Rustanti, Ninik (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Kombucha is a fermented beverage known for its various health benefits, including antibacterial activity. This study aims to evaluate the antibacterial potential of mango ginger (Curcuma mangga)-based kombucha against Escherichia coli and Salmonella typhi, as well as to analyze the effect of fermentation duration on the physicochemical properties of kombucha. Fermentation was conducted for 5, 7, 10, and 14 days, with total acidity, pH, and antibacterial activity measurements using the well diffusion method. The results showed total acidity increased as fermentation progressed, while pH decreased. Antibacterial tests demonstrated that mango ginger kombucha exhibited inhibitory activity against Escherichia coli and Salmonella typhi, with the largest inhibition zones observed on day 10 of fermentation (8.2 mm for Escherichia coli and 9.2 mm for Salmonella typhi). Although its inhibitory effect was moderate compared to the positive control (ciprofloxacin), these findings suggest the potential of mango ginger kombucha as a functional beverage with antibacterial properties. Further research is needed to identify the active compounds responsible for its antimicrobial activity and to optimize the fermentation process to enhance its effectiveness.